2007
DOI: 10.1002/lapl.200610124
|View full text |Cite
|
Sign up to set email alerts
|

Transition rate dependence on the atom charge states, Z

Abstract: Here are shown two different transition rates, one obtained in the ADK‐theory [1,2] and the other one for ADK result with turning point corrected with the Coulomb interaction – let us denote it cADK [1, 3], in both cases the changing of charge states Z of atoms was performed. If plotted for the fields from 1012 W/cm2 to 1017 W/cm2 and for Z = 1 to Z = 10, the two variants give behavior which were not predicted before, Fig. 1 and Fig. 2, showing in the cADK case pick which is not shown in the ADK case. But from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Ristić et al [32,33] improved the tunnelling model by more accurate account of the positions of the turning points. The tunnelling rate dependence on the ion charge number, Z, is more accurately considered in [34].…”
Section: Introductionmentioning
confidence: 99%
“…Ristić et al [32,33] improved the tunnelling model by more accurate account of the positions of the turning points. The tunnelling rate dependence on the ion charge number, Z, is more accurately considered in [34].…”
Section: Introductionmentioning
confidence: 99%
“…It is definitely shown [1][2][3][4][5][6][7][8][9][10] that for low frequency laser fields one of the mostly used models is based on the tunneling regime: external field, due to its long duration, leads to the formation of the barrier through which electron can tunnel out. Among theories using this model the ADK-theory [1] is widely recognized.…”
Section: Introductionmentioning
confidence: 99%
“…As we have recently shown that the momentum of the ejected electron influences the transition rate in the case of ADK-theory [2,[7][8][9], we are now examining how the change of atom charge Z [8], when including non-zero momentum, contributes to transition rates for circularly polarized laser fields. Here, we are devoloping further the observations from our earlier work which included the ADK-theory.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical framework was given by Keldysh [1]; it was further developed, resulting in emerging of the ADK--theory (Ammosov, Delone, Krainov) [2]. Some recent papers [3][4][5] improved it further, but in them the authors always assumed that the ionized electrons are leaving the atom with zero initial momentum (except say in [6,7]). Except for aforementioned papers, in [8] it was given thorough calculation of dependence of the initial momentum on the parabolic coordinate η.…”
Section: Introductionmentioning
confidence: 99%